Electric wetting of ZnO surface - Tan, Jasmine Mei Zhen. (2010)
Wettability is an important property of solid materials and is governed by both the surface chemical composition and the surface geometrical structure. The modifiable wetting properties has aroused much interest due to the wide practical applications in distinct technological industry such as microelectronics, food technology and cell manipulation. Hydrophobic surface refers to a surface with water contact angle of larger than 90° whereas a water contact angle smaller than 90° is referred to hydrophilic surface.